The AI-shift: how Europol is leveraging artificial intelligence to combat serious organised crime and terrorism - Valér Dános (Belügyi Szemle)
Aim: The aim of this article is to highlight the importance of leveraging Artificial Intelligence (AI) in law enforcement to combat serious organised crime and terrorism, while ensuring responsible and accountable use of AI tools through collaboration and knowledge-sharing among European law enforcement agencies.